1993
DOI: 10.1002/hep.1840180426
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of hemoglobin saturation in the liver with near-infrared spectroscopy

Abstract: To quantify the changes in oxygen saturation of hemoglobin in the liver in hypoxia and liver transplantation, we applied a novel method using near-infrared spectroscopy. Instead of the conventional two-wave-length method, we obtained near-infrared data from a wide spectral range of 700 nm to 1,000 nm with continuous-wave spectroscopy. To correct the flattened spectral shape caused by photon scattering in living tissue, we then applied an equation taking into account the relationship between absorber concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 22 publications
2
50
0
Order By: Relevance
“…Several authors have reported on NIRS measurement of liver tissue oxygenation. [9][10][11][22][23][24][25] Most of these studies were performed in animals, with the NIRS probe attached to the liver surface after laparotomy. The investigators mainly studied relative changes of liver tissue oxygenation during naso-gastric feeding, induced hypovolemia, low cardiac output, graded hypoxia or hepatic vascular in-flow occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported on NIRS measurement of liver tissue oxygenation. [9][10][11][22][23][24][25] Most of these studies were performed in animals, with the NIRS probe attached to the liver surface after laparotomy. The investigators mainly studied relative changes of liver tissue oxygenation during naso-gastric feeding, induced hypovolemia, low cardiac output, graded hypoxia or hepatic vascular in-flow occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the fibers allowed us to perform NIRS measurements simultaneously with 31 P-MRS measurements while the piglets were in the magnet. We used a white plate as a reference to convert the spectrum to an absorption spectrum (20).…”
Section: Methodsmentioning
confidence: 99%
“…10,11 The use of NIRS for evaluating hepatic tissue oxygenation is limited to the authors 12 and one main group in Japan. 13 However, there is no basic experimental work to define the significance of the NIRS signal from the liver parenchyma and its relationship with liver blood flow and oxygen supply. As a prelude to human organ transplant work, we have therefore evaluated the application of NIRS for the measurement of hepatic tissue oxygenation and perfusion in a large animal model with hepatic vascular inflow occlusion and graded hypoxia.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%